Covered vs bare stent for distal malignant biliary obstruction due to primary common biliary cancer. Issue 3 (22nd January 2021) - Tang, Ling; Bao, Kai-Hu; Xu, Yuan-Shun; Liu, Peng-Hui
Abstract : Abstract: This study was designed as a means of comparing the clinical efficacy and long-term outcomes of covered vs bare stent insertion as a treatment for distal malignant biliary obstruction (DMBO) caused by primary common biliary cancer (PCBC). This retrospective study was designed using data collected between January 2012 and December 2019 to assess the short- and long-term outcomes in patients with DMBO caused by PCBC treated by inserting either bare or covered stents were compared. Ninety two patients with DMBO caused by PCBC were divided between bare (n = 51) or covered (n = 41) stent groups. Technical success rates in both groups were 100%. Clinical success of bare vs covered stent use were 96.1% and 97.6% ( P  = 1.00). Stent dysfunction was seen in 17 and 6 patients in the bare and covered stent groups, respectively ( P  = .04). The median stent patency for bare and covered stents was 177 and 195 days, respectively ( P  = .51). The median survival was 188 and 200 days in the bare and covered stent groups, respectively ( P  = .85). For patients with DMBO caused by PCBC, using bare vs covered stents yields similar clinical efficacy and long term outcomes.